2017
DOI: 10.1177/2309499017690459
|View full text |Cite
|
Sign up to set email alerts
|

Is neck massage safe? A rare case of tetraplegia and spinal shock after neck manipulation

Abstract: Neck manipulation is associated with spinal cord injury. However, occurrence of such cases is infrequent. This article presents a 33-year-old gentleman who sustained acute tetraplegia after neck manipulation. The aim of this case report is to create awareness that vigorous neck manipulation could cause injury to the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Regarding treatment, our review of the literature has shown that the two attitudes are the same, namely a surgical approach [ 11 - 13 ] or conservative treatment [ 9 , 14 , 15 ], associated in all cases with boluses of corticosteroids with analgesic treatment. Staying in ICU depends on the general clinical state of the patient at admission.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment, our review of the literature has shown that the two attitudes are the same, namely a surgical approach [ 11 - 13 ] or conservative treatment [ 9 , 14 , 15 ], associated in all cases with boluses of corticosteroids with analgesic treatment. Staying in ICU depends on the general clinical state of the patient at admission.…”
Section: Discussionmentioning
confidence: 99%
“…All reported CEH cases have generally occurred posteriorly or posterolaterally. [5][6][7][8][9][10][11][12][13][14][15] The pathological mechanism of spinal epidural hematoma remains still unclear but the bleeding from the epidural vein plexus is the most widely accepted hypothesis for the mechanism of hematoma formation. 17 The most probable association could be explained by the anatomical lack of valves in the epidural venous system.…”
Section: Discussionmentioning
confidence: 99%
“…19 Cervical laminectomy has been the most described surgical procedure for decompression of spinal cord in patients with CEH. 5,7,[8][9][10]13 However, standard laminectomy has also been reported to result in late cervical deformities such as kyphosis or segmental instability. 20 Full recovery from all neurological deficits was reached by our patient some days after the emergency decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment should be performed in patients with severe neurological deficits or progressive severe symptoms. In a case reported by Ling et al [7], surgery was performed after the patient was admitted for tetraplegia after neck manipulation. These authors believed an earlier surgical intervention would have delivered a better outcome and improvement.…”
Section: Discussionmentioning
confidence: 99%